GIANT MULTIPLE INTRA-ABDOMINAL HYDATID CYSTS - Nadeem, Naila; Khan, Hassan; Fatimi, Saulat; Ahmad, Mohammad Nadeem (Journal of Ayub Medical College Abbottabad, 2006)
Hydatid disease is endemic in the cattle grazing areas particularly Australia, New-Zealand, Middle East, India, Africa, South America and Turkey 1. It is a parasitic infection caused by the cestode tapeworm Echinoccocus granulosus. The dogs are the definitive host and the adult worms are found in their small intestine. Humans get infected either by contact with the definitive host or by consuming vegetables and water contaminated with the hydatid ova 2. In humans the hydatid disease commonly involves the liver (75%) and the lungs (15%). The remaining (10-15%) of the cases include the other regions of the body 1. The disseminated intra-peritoneal hydatid disease is a very rare finding 1. We report such a presentation wherein the abdominal cavity is seen to contain multiple hydatid cysts.